2021
DOI: 10.1039/d1tb00178g
|View full text |Cite
|
Sign up to set email alerts
|

3D printed polycaprolactone/beta-tricalcium phosphate/magnesium peroxide oxygen releasing scaffold enhances osteogenesis and implanted BMSCs survival in repairing the large bone defect

Abstract: Fabricate a MgO2-contained scaffold by 3D printing to improve ischemia and hypoxia in bone defect area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Severe hypoxia usually suppresses proliferation and osteogenic differentiation of BMSCs and impedes bone defect reconstruction [ 28 ]. In the treatment of large bone defects, ischemia and hypoxia in the bone defect area remain a thorny issue [ 29 ]. Here, hypoxic BMSCs presented increased apoptosis and oxidative stress and reduced mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Severe hypoxia usually suppresses proliferation and osteogenic differentiation of BMSCs and impedes bone defect reconstruction [ 28 ]. In the treatment of large bone defects, ischemia and hypoxia in the bone defect area remain a thorny issue [ 29 ]. Here, hypoxic BMSCs presented increased apoptosis and oxidative stress and reduced mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sr 2+ enhances the synthesis of VEGF and ANG1 in MSCs [ 94 ]. Moreover, Ca 2+ , Mg 2+ , Zn 2+ and Sr 2+ are each shown to promote the migration [ [103] , [104] , [105] ] and osteo-differentiation [ 27 , [30] , [31] , [32] , [33] , 94 ] of MSCs. However, the collaborative action of the multi-ions on MSC migration and angio/osteo-genic response remains elusive, especially in the presence of MΦs.…”
Section: Resultsmentioning
confidence: 99%
“…64,81,82,65,5 Peng et al fabricated the PCL/β-TCP/MgO 2 scaffold and found that when the weight ratio of MgO 2 was 10%, the scaffold's Young's modulus was 102.01 MPa, matching the property of natural bones and nearly twice that of the control group containing no MgO 2 or MgO powder. 82 Zhang et al reported that adding magnesium as well as POSS synergistically enhanced the GelMA/TCS hydrogel's tensile strength by almost 2-fold and reached 310.8 ± 11.5 kPa. 81 Gu et al found the young's modulus and maximum load stress of TCP scaffold containing 1 wt % MgO were 930.65 ± 163.79 MPa and 30.69 ± 3.90 MPa, respectively, which were much higher than that of the pure TCP scaffold.…”
Section: Effects Of Magnesium Ions On Bone Tissue Engineeringmentioning
confidence: 99%